(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
This project shows all the methodology used to design equipment for the physical therapy of patients suffe-ring from low-level spinal cord injury, cauda equine injury or herniated disc, which seeks to provide a more efficient physiotherapy that currently offered, in this document contains all the equipment design process fo-llowing the standards established for the manufacture of these electro mechanical equipment.